Wybór Ambrożego Aureliusza na biskupa Mediolanu: cud, czy celowe działanie Walentyniana I? - Spychała, Dariusz (Poznańskie Towarzystwo Przyjaciół Nauk, 2014)
Aurelius Ambrosius is a characteristic example of an official of the imperial administration who made a clerical career in the early days of Christianization of the Empire. His life was full of unexpected events. Born into a Christian family, he still put off the moment of baptism – a common custom, yet not recommended by the Church. His stable career path changed radically when Ambrosius was elevated to the rank of Bishop of Milan, which entailed the violation of virtually all canons of ecclesiastical law. All that took place in circumstances which are more akin to literary fiction than reality (with the voice of an anonymous child saying that Ambrosius be anointed a bishop).
The appointment of Aurelius Ambrosius as the bishop of Milan: a miracle or a strategem of Valentinian I?
Keywords: bishop; empire; church